2022
DOI: 10.3390/app12031358
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning-Based Automatic Segmentation of Mandible and Maxilla in Multi-Center CT Images

Abstract: Sophisticated segmentation of the craniomaxillofacial bones (the mandible and maxilla) in computed tomography (CT) is essential for diagnosis and treatment planning for craniomaxillofacial surgeries. Conventional manual segmentation is time-consuming and challenging due to intrinsic properties of craniomaxillofacial bones and head CT such as the variance in the anatomical structures, low contrast of soft tissue, and artifacts caused by metal implants. However, data-driven segmentation methods, including deep l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 52 publications
0
10
1
Order By: Relevance
“… 29 31 32 Some studies have used deep learning and machine learning techniques to diagnose and classify temporomandibular joint diseases, perform maxillary and mandible segmentation, and guide oral and maxillofacial surgeons with acceptable diagnostic accuracy. 28 33 34 In the orthodontics field, some studies have proposed deep learning frameworks for cluster-based segmentation and automatic landmark detection in cephalometric analysis. 35 36 …”
Section: Discussionmentioning
confidence: 99%
“… 29 31 32 Some studies have used deep learning and machine learning techniques to diagnose and classify temporomandibular joint diseases, perform maxillary and mandible segmentation, and guide oral and maxillofacial surgeons with acceptable diagnostic accuracy. 28 33 34 In the orthodontics field, some studies have proposed deep learning frameworks for cluster-based segmentation and automatic landmark detection in cephalometric analysis. 35 36 …”
Section: Discussionmentioning
confidence: 99%
“…The success of deep learning (DL) in computer vision has led to the increased application of artificial intelligence (AI) in medical image analysis [1,2]. DL-based AI models have been applied to clinical vision applications, such as lesion detection, classification, and segmentation, thereby outperforming conventional machine learning models [3][4][5][6]. Moreover, explainable AI (XAI) allows users to interpret and trust the results predicted by the AI model [7].…”
Section: Introductionmentioning
confidence: 99%
“…It may halt the possible implementation of the general model into routine clinical care if it does not have a consistent accuracy for site-specific use. To obtain a comparable external test performance to the internal tests, reported studies involving training datasets from multicenter to develop the detection algorithm demonstrated that it can either underperform ( 10 12 ) or have a comparable performance to the internal test ( 11 , 13 ) without any unanimous conclusion reached, which may be explained by the differences of the datasets scale and the numbers of dataset origins ( 14 ). Using local images for model training seems to be another way to obtain a site-specific used tool for diagnosis.…”
Section: Introductionmentioning
confidence: 99%